تحليل الكتاب الدراسي "تيسير اللغة العربية" المجلد الثاني لشريفة نور حفظية لدى تلاميذ الصف الثامن في المدرسة المتوسطة المتحدة الإسلامية الهجرة 2 دلي سيردانج - Buyah Pasaribu; Zulfina Zulfina; Salamuddin Salamuddin (Jurnal Al-Hibru, 2024)
This study aims to determine whether the textbook "تيسير اللغة العربية" Volume 2 by Syarifah Nurhafziyah, S.Pd for Class VIII, has met the criteria of a good textbook when viewed from the material that has been summarized in, as well as knowing what the advantages and disadvantages of the book are. Methodologically, this research uses Library Research or library research, namely a series of activities related to library data collection methods, while the type of research used is an analysis of book presentation. And the main data source in this research is the textbook "تيسير اللغة العربية" Volume 2 by Syarifah Nurhafziyah, S.Pd Class VIII SMP-IT Al-Hijrah 2 Deli Serdang. After conducting research on existing materials, the researchers concluded that: (a) From the aspect of Selection, the selection of the book's material is in accordance with the purpose of writing the book and the level of proficiency of the reader / beginner, because of the simplicity of language and the provision of examples that are easy to understand. (b) From the aspect of Material Preparation is fairly good, because it prioritizes the more basic rules, and (c) From the aspect of Presentation, the material presented using language and delivery methods that are easily understood by readers, especially beginners and as for the advantages of the book, namely; (1) The title is enough to attract the attention of beginners, (2) the material is arranged systematically, (3) the use of simple and easy-to-understand language, (4) the form of the book is simple and easy to understand.